(untitled) (Baghdad Science Journal, 2025)
Biosorpion of lead (Pb), Cadmium (Cd) and Nickl(Ni) by dried biomass of Chara sp. for sample of BMP was used as alternative approach of conventional method. The range of removal percentages was between 92-97%, 70-98.7% and 46.6-96.6% for Pb, Cd and Ni respectively at 3h.Treatment time, with 300-500 mg dried weight from Chara sp. powder at pH 4, with 60 rpm at shaker. FTIR analysis showed the active groups which are responsible for sequestration of heavy metals represented by carboxyl, hydroxyl alkyl, amine and amide. The Biosorption equilibrium experiment for elements showed that the highest sorption percentage for three elements was, Pb 96.6% after 30 minute, for Cd was 100% after 15 minute and 40% to Ni after 75 minute, while the biosorption equilibrium by using Chara sp. was at 90 minute for Pb and Ni.